PENGARUH INOVASI PRODUK, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI PT. CITRA RASA COKLAT CHOCO BAKERY CABANG TEMBUNG - Manzilah Putri Daulay; Wulandari, Sari; Yuliana, Yayuk; Rahmat, Muhammad (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2024)
This study aims to analyze the effect of product innovation (X₁), product quality (X₂) and service quality (X₃) on purchasing decisions (Y) at PT Citra Rasa Coklat Choco Bakery Tembung Branch. The number of respondents in this study were 85 respondents. Data collection was carried out by distributing questionnaires or questionnaires. All analyses contained in this study used the SPSS (Statistical Package for Social Sciences) 24.0 program. Based on the results of multiple linear regression Y = 4.145 + 0.381X1 + 0.088X2 + 0.307X3 + e. These results illustrate that product innovation, product quality, and service quality have a significant effect on purchasing decisions. To see whether the hypothesis in the statement that product innovation partially has a positive and significant effect on purchasing decisions can be seen from the value of the t-count> t-table value 4.147> 1.66 at a significant 0.000 <0.05 in other words H0 is rejected and H1 is accepted. The results of research on product quality variables state that product quality partially has a positive and significant effect on purchasing decisions as evidenced by the value of t-count> t-table, 3.024> 1.66 at a significant 0.031 <0.05 in other words H0 is rejected and H2 is accepted. Likewise, the service quality variable partially has a positive and significant effect with a t-count> t-table value, 4.470> 1.66 at a significant 0.000 <0.05 in other words H0 is rejected and H1 is accepted. It can also be seen that simultaneously product innovation, product quality, and service quality have a positive and significant influence on purchasing decisions at PT Citra Rasa Coklat Choco Bakery Tembung Branch with the value of F count> F tabel, namely 43.615> 2.98 in other words H0 is rejected and H4 is accepted. The level of the coefficient of determination reaches 0.603 where the independent variable has an influence of 60.30% on the dependent variable and the remaining 39.70% is influenced by other factors not examined